2020
DOI: 10.1002/pmic.201900383
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin Silencing Induces Different Processes in Different Breast Cancer Cell Lines

Abstract: Transgelin is a protein reported to be a marker of several cancers. However, previous studies have shown both up‐ and down‐regulation of transgelin in tumors when compared with non‐tumor tissues and the mechanisms whereby transgelin may affect the development of cancer remain largely unknown. Transgelin is especially abundant in smooth muscle cells and is associated with actin stress fibers. These contractile structures participate in cell motility, adhesion, and the maintenance of cell morphology. Here, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…22 Growth factor-stimulated proliferation of human umbilical vein and aortic endothelial cells was found to be highly dependent on IQGAP1. 23 The non-detection of TAGLN we observed (Figure 1(f)) from the MCF-7 cells coincides with the findings of Dvorakova et al 24 Prior studies stated that PIP2 and IQGAP1 are both expressed in MCF-7 cells. 25,26 However, the non-existence of variances observed with PIP2 and IQGAP1 levels between TAGLN knockdown and control cells (Figure 1(f)) means that no coactions among TAGLN, PIP2, and IQGAP1 have transpired.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…22 Growth factor-stimulated proliferation of human umbilical vein and aortic endothelial cells was found to be highly dependent on IQGAP1. 23 The non-detection of TAGLN we observed (Figure 1(f)) from the MCF-7 cells coincides with the findings of Dvorakova et al 24 Prior studies stated that PIP2 and IQGAP1 are both expressed in MCF-7 cells. 25,26 However, the non-existence of variances observed with PIP2 and IQGAP1 levels between TAGLN knockdown and control cells (Figure 1(f)) means that no coactions among TAGLN, PIP2, and IQGAP1 have transpired.…”
Section: Resultssupporting
confidence: 90%
“…Growth factor‐stimulated proliferation of human umbilical vein and aortic endothelial cells was found to be highly dependent on IQGAP1 23 . The non‐detection of TAGLN we observed (Figure 1(f)) from the MCF‐7 cells coincides with the findings of Dvorakova et al 24 . Prior studies stated that PIP2 and IQGAP1 are both expressed in MCF‐7 cells 25,26 .…”
Section: Resultssupporting
confidence: 88%
“…These results are consistent with our data in vitro, which showed that TAGLN expression is higher in TNBC cells than in mammary duct cells; these ndings suggest that TAGLN is expressed differently in different types of BC, which may be related to its speci c context [31]. TAGLN expression in TNBC cells is also different, which may be related to its DNA methylation [32]. The growth curve data we generated indicate that compared to the control conditions, TAGLN overexpression promoted MDA-MB-468 cell growth, and TAGLN knockdown attenuated SUM159 and Hs578T cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies revealed that TAGLN expression increases after UV irradiation [ 12 ]. TAGLN is an actin-binding protein that affects the dynamics of the actin cytoskeleton, regulating cell migration and movement [ 13 , 14 ]. However, few studies have investigated whether TAGLN can regulate UV-induced skin aging and whether a relationship exists between TAGLN and ZEB1.…”
Section: Introductionmentioning
confidence: 99%